2018
DOI: 10.5812/jhealthscope.14561
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Short Form of Situational Temptation Scale for Smoking Cessation among Iranian Workers Based on Transtheoretical Model

Abstract: Background: Situational temptations are important key points for smoking cessation. However, temptation to engage in smoking across different situations is yet challenging. In Iran, there is no measurement to assess situational temptations among workers. Objectives: The current study aimed at psychometrically evaluating the short form of situational temptations scale for smoking cessation based on transtheoretical model. Methods: By stratified random sampling method, 218 male current smoking automobile factory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The results of CFA showed that the construct validity of the questionnaire was acceptable (RMSEA = 0.006, GFI = 0.973, AGFI = 0.955). Also, Cronbach’s alpha was 0.80 and the reliability of the instrument was confirmed [ 49 ]. The results of the CFA in Can’s study showed that the questionnaire of challenges to stopping smoking with 21 items and two factors had the acceptable goodness of fit indices (RMSEA = 0.078, RMR = 0.011, CFI = 0.94, NFI = 0.90, IFI = 0.94).…”
Section: Discussionmentioning
confidence: 99%
“…The results of CFA showed that the construct validity of the questionnaire was acceptable (RMSEA = 0.006, GFI = 0.973, AGFI = 0.955). Also, Cronbach’s alpha was 0.80 and the reliability of the instrument was confirmed [ 49 ]. The results of the CFA in Can’s study showed that the questionnaire of challenges to stopping smoking with 21 items and two factors had the acceptable goodness of fit indices (RMSEA = 0.078, RMR = 0.011, CFI = 0.94, NFI = 0.90, IFI = 0.94).…”
Section: Discussionmentioning
confidence: 99%